KAJIAN NUMERIK PENGARUH VARIASI SUDUT STAGGER DAN DIAMETER SILINDER SIRKULAR DI SISI ADVANCING BLADE TERHADAP KINERJA TURBIN AIR SAVONIUS BERSUDU KOMBINASI MYRING N=1 DAN N=2 - Firdaus Styo Fathoni; Priyo Agus Setiawan; Daisy Dwijati K.R.A (Politeknik Perkapalan Negeri Surabaya, 2020)
Indonesia has a great potential to use water currents as an energy source that can be convertedinto electricity. Savonius water turbines can be used as its solution to make it. Its performance can be improvedby modifying its combined blades with myring n=1 and n=2 and also by adding a circular cylinder on it. TheComputational Fluid Dynamics (CFD) method with Ansys 17.2-Fluent and Tecplot software are chosen and usedfor its flow characteristics study produced by the turbine. Gambit software is also used to create geometry anddomain models. The boundary condition of the model include the inlet as the input properties area with an initialvelocity of 0.22 m/s as analysis limitation of control surface on the test model. The modification include the useof combined blade with myring n=1 and n=2. One circular cylinder is added in front of the advancing blade sothat the flow velocity will be higher and its efficiency can be increased. Circular cylindrical diameters are variousi.e. ds/D=0.2; 0.3 and 0.4 with 0?, 30? and 60? stagger elevation angles. The results obtained from this researchare the values of torque coefficient (Cm), power coefficient (Cp), pressure distribution and fluid flowcharacteristics. Turbine performance has the highest increase (35.86%) on ds/D =0.4 with 60? stagger elevationangle variation. The greatest decrease (30.11%) occured on ds/D=0.4 0? stagger elevation angle variation withoutusing circular cylinder.